Pengaruh Budaya Sekolah, Hasil Belajar PAI, dan Pola Asuh Orang Tua Terhadap Pembentukan Karakter Siswa di SMA Negeri 4 Surabaya - Suhaidin Dena; Nelud Drajatul Aliyah; Didit Darmawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explore the influence of school culture, parenting patterns and the results of Islamic religious education on the formation of student character at SMA Negeri 4 Surabaya. A school culture that is based on ethical and moral values as the main pillar creates an environment that supports the development of student character. Parental parenting styles, which include attention, emotional support, and open communication, are identified as important factors for shaping student character and PAI learning outcomes equip students with a deep understanding of life norms, morality, and ethics which become a strong foundation for character formation. positive. Three independent variables that determine student character will be the focus of this research. With a quantitative approach using regression analysis methods, this research proves that school culture and parental parenting patterns significantly contribute to the formation of student character. The findings of this research provide a strong theoretical basis and have practical implications for educational policy development. This research provides guidance for schools and parents to design educational strategies to support students' positive development. The conclusions of this research provide a basis for implementing educational policies that support student character at SMA Negeri 4 Surabaya.